1995
DOI: 10.1080/01496399508010380
|View full text |Cite
|
Sign up to set email alerts
|

Distillation with Chemical Reaction and Apparatus Selection

Abstract: Reactive distillation was studied practically and theoretically for the esterification of succinic anhydride with methanol to produce in a first step monomethyl succinate and in a second one dimethyl succinate and water. I t was shown that simulations using the ASPEN PLUS rigorous distillation model RADFRAC corresponds with experimental data quite well. With this fundament further calculations were performed simulating several kinds of reactive and distillation equipment. On basis of this, a n apparatus select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In particular, for succinic acid or succinic derivatives, there is lack of information on phase equilibria in multicomponent systems. Simulations in Aspen Plus ® for methyl succinate production by RD [25], showed that only qualitative trends can be obtained using available thermodynamic parameters. In the case of DES, generalized group contribution methods have been used to calculate activity coefficients in mixtures, but predictions did not agree with experimental data [26,27].…”
Section: Introductionmentioning
confidence: 97%
“…In particular, for succinic acid or succinic derivatives, there is lack of information on phase equilibria in multicomponent systems. Simulations in Aspen Plus ® for methyl succinate production by RD [25], showed that only qualitative trends can be obtained using available thermodynamic parameters. In the case of DES, generalized group contribution methods have been used to calculate activity coefficients in mixtures, but predictions did not agree with experimental data [26,27].…”
Section: Introductionmentioning
confidence: 97%